Education and sustainability in the rural environment: a case study on the perception of family farmers (Research, Society and Development, 2020)
The objective of the present case study was to verify the perception and practices of small family farmers regarding the aspects of conservation of springs in their rural property, as well as to identify the rural training activities offered in their territorial space. The work was carried out in 99 rural properties of family farmers in the Ponte Alta Rural Nucleus, Administrative Region of Gama, in the City of Brasília, Federal District - Brazil. This research is methodologically characterized as quantitative, exploratory and descriptive. Data collection was carried out through the application of a semi-structured questionnaire, containing questions that referred to the perception and behavior of the interviewed farmers on the theme under analysis and characterization of the social profile. Based on the results, it is clear that less than 50% of the interviewees carry out spring recovery and conservation practices. Among the farmers who tried to recover their springs, 27.27% just surrounded the spring, another 27.27% just reforested and 27.27% recovered through planting. The lack of knowledge about the importance of recovering springs in rural properties is a reality. Thus, environmental education becomes an important tool for rural producers to become aware of environmental aggravation and, at the same time, to learn about the methods for appropriate preservation and conservation. Production of native seedlings, Fruit and Organic Agriculture were registered as the main training desires pointed out by family farmers, which may lead to the perception of a certain degree of environmental awareness among small farmers in the region where the study was carried out.